Contributions of Advanced Practice Nurses With a DNP Degree During Palliative and End-of-Life Care of Children With Cancer. (January 2015) - Hendricks-Ferguson, Verna L.; Akard, Terrah Foster; Madden, Jennifer R.; Peters-Herron, Alberta; Levy, Robyn
The doctorate in nursing practice (DNP) degree is recommended as the terminal degree for advanced practice nurses by 2015. Improvement in the quality of palliative and end-of-life care for children with cancer is recognized as a health care priority. The purpose of this article is to describe: ( a ) how the American Association of Colleges of Nursing's 8 core elements and competencies can be used by DNP-advanced practice nurses in pediatric oncology settings and ( b ) the DNP-advanced practice nurses' leadership role to advocate translation of evidence in the care of pediatric oncology patients and to promote interdisciplinary collaboration to improve health care outcomes for pediatric oncology patients.